Protistan plankton communities in the Galápagos Archipelago respond to changes in deep water masses resulting from the 2015/16 El Niño - Erika F. Neave; Harvey Seim; Scott M. Gifford; Olivia Torano; Zackary I. Johnson; Diego Páez‐Rosas; Adrian Marchetti (Environmental Microbiology, 2022)
Summary The Galápagos Archipelago lies within the Eastern Equatorial Pacific Ocean at the convergence of major ocean currents that are subject to changes in circulation. The nutrient‐rich Equatorial Undercurrent upwells from the west onto the Galápagos platform, stimulating primary production, but this source of deep water weakens during El Niño events. Based on measurements from repeat cruises, the 2015/16 El Niño was associated with declines in phytoplankton biomass at most sites throughout the archipelago and reduced utilization of nitrate, particularly in large‐sized phytoplankton in the western region. Protistan assemblages were identified by sequencing the V4 region of the 18S rRNA gene. Dinoflagellates, chlorophytes and diatoms dominated most sites. Shifts in dinoflagellate communities were most apparent between the years; parasitic dinoflagellates, Syndiniales , were highly detected during the El Niño (2015) while the dinoflagellate genus, Gyrodinium , increased at many sites during the neutral period (2016). Variations in protistan communities were most strongly correlated with changes in subthermocline water density. These findings indicate that marine protistan communities in this region are regimented by deep water mass sources and thus could be profoundly affected by altered ocean circulation.